Recreational Cannabis Use: Regulatory Aspects, Public Opinion and Concerns for Public Health - Scopetti, Matteo; Padovano, Martina; Peruch, Michela; Concato, Monica; Livieri, Tommaso; Radaelli, Davide; D'Errico, Stefano (Current Pharmaceutical Biotechnology, 2023)
Cannabis represents the most used substance in the young population after alcohol and tobacco. The consumption of the substance undoubtedly represents an emerging public health issue, and the regulatory aspects are quite heterogeneous. Alternatives to drug prohibition, such as legalization or decriminalization, are a topic of growing debate among researchers, policy makers and the public. Limiting harmful use and combating illicit trafficking are the main objectives of legalization for recreational purposes, although liberalization raises critical issues that have not yet been resolved despite the experience gained in many countries. In the context of legalization, it is essential to allow the lawful production of cannabis, guarantee a supply of controlled quality cannabis, and ensure that the population understands the risks associated with the consumption of the substance. At the same time, it is essential to protect the safety and health of the population by limiting access to cannabis and preventing accidental exposure to fragile categories and children. Incomplete knowledge of law enforcement can create further complications. Incomplete knowledge of the implementation of the laws can create further complications; therefore adequate information must be favored. Scientific evidence helps to understand the potential harms and benefits of cannabis, but the impact of legalization - even in terms of reducing consumption - is not clearly documented. So, far more efforts need to be made in the future to broaden awareness of the general population on the recreational use of cannabis.
Keywords: lawful production